Hubungan Internasional: Sebagai jawaban atas kemiskinan di Afrika - Adiza, Naufal; Rungga, Rafi (Jurnal Pendidikan Ekonomi Undiksha, 2025)
You said: The problem of poverty in Africa has been a complex and long-standing issue, even though the majority of countries on the continent have achieved independence. This is influenced by inhibiting factors that directly or indirectly affect economic growth in the African region. In this paper, the author presents his opinions and ideas regarding conditions in Africa that have hampered economic growth in their region to date. In this paper, the author uses literature from various existing sources. Therefore, in selecting data using references from the sources listed. Economic growth in the African region itself has actually progressed over the past few decades. Through bilateral cooperation on the international stage, they have been able to develop regions that were previously considered underdeveloped countries into developing countries, which indicates a change in the welfare of their people.